2020
DOI: 10.1371/journal.pone.0234217
|View full text |Cite
|
Sign up to set email alerts
|

Muscle architecture, voluntary activation, and low-frequency fatigue do not explain the greater fatigue of older compared with young women during high-velocity contractions

Abstract: Although high-velocity contractions elicit greater muscle fatigue in older than young adults, the cause of this difference is unclear. We examined the potential roles of resting muscle architecture and baseline contractile properties, as well as changes in voluntary activation and low-frequency fatigue in response to high-velocity knee extensor work. Vastus lateralis muscle architecture was determined in quiescent muscle by ultrasonography in 8 young (23.4±1.8 yrs) and 8 older women (69.6±1.1). Maximal volunta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
(149 reference statements)
0
5
0
Order By: Relevance
“…Previous work has consistently shown greater fatigue in older than young adults in response to high‐velocity isokinetic (i.e., ≥240°s −1 ) or isotonic contractions (i.e., against a low‐load equivalent to ~20% MVIC) of the knee extensor muscles (Callahan & Kent‐Braun, 2011; Dalton et al., 2012, 2015; Fitzgerald et al., 2020; Sundberg, Kuplic, et al., 2018; Sundberg et al., 2019), as well as other muscles groups (Dalton et al., 2010; Wallace et al., 2016). A systematic review and meta‐analysis indicated greater muscle fatigue in older than young adults in studies where dynamic contractions were performed or muscular power was used as the index of fatigue (Christie et al., 2011).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Previous work has consistently shown greater fatigue in older than young adults in response to high‐velocity isokinetic (i.e., ≥240°s −1 ) or isotonic contractions (i.e., against a low‐load equivalent to ~20% MVIC) of the knee extensor muscles (Callahan & Kent‐Braun, 2011; Dalton et al., 2012, 2015; Fitzgerald et al., 2020; Sundberg, Kuplic, et al., 2018; Sundberg et al., 2019), as well as other muscles groups (Dalton et al., 2010; Wallace et al., 2016). A systematic review and meta‐analysis indicated greater muscle fatigue in older than young adults in studies where dynamic contractions were performed or muscular power was used as the index of fatigue (Christie et al., 2011).…”
Section: Discussionmentioning
confidence: 97%
“…We did not include a measure of voluntary activation in the current study, which could have provided useful insight as to the ability of participants to fully activate the knee extensor muscles while supine inside the MR scanner. This decision was based upon the weight of evidence in the literature indicating that deficits in voluntary activation do not likely contribute to age‐related differences in muscle fatigue (Dalton et al., 2010; Fitzgerald et al., 2020; Sundberg, Kuplic, et al., 2018). Thus, although we cannot rule out the presence of voluntary activation failure in the current study, this possibility seems unlikely given previous work in this area, as well as the robust associations between H + and fatigue observed in the present study in both groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Briefly, the participants completed a short set of practice trials to familiarize themselves with the testing protocol, followed immediately by three maximal repetitions per test (1 min rest between repetitions). Finally, an isokinetic knee extensor endurance test comprised of 120 maximal voluntary contractions at 240°/s (one every 2 s for 4 min) was performed to measure the total work (i.e., a measure of absolute endurance) as previously described (Fitzgerald et al., 2020 ). In addition, we also determined the percent change in peak torque measured during the first 20 repetitions relative to the last 20 repetitions (i.e., relative endurance).…”
Section: Methodsmentioning
confidence: 99%